Website premia for extensive margins of international firm activities: Evidence for SMEs from 34 countries - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2022)
This paper uses firm level data from the Flash Eurobarometer 421 survey conducted in June 2015 in 34 European countries to investigate the link between having a website and international firm activities in small and medium sized enterprises (SMEs). We find that firms which are present in the web do more often export, import, engage in research and development cooperation with international partners, work as subcontractors for firms from other countries, use firms in other countries as subcontractors, and perform foreign direct investments - both inside and outside the European Union. The estimated website premia are statistically highly significant after controlling for firm size, country, and sector of economic activity. Furthermore, the size of these premia can be considered to be large. Internationally active firms tend to have a website.
Keywords: D22; F14; F23; L25; 330; Website premia; international firm activities; Flash Eurobarometer 421